Sintesis dan Karakterisasi Membran Selulosa Asetat dari Tandan Kosong Kelapa Sawit (Synthesis and Characterization of Cellulose Acetate Membranes from Oil Palm Empty Fruit Bunches) - Apriani, Rina; Rohman, Taufiqur; Mustikasari, Kamilia (Jurnal Riset Industri Hasil Hutan, 2017)
The research of synthesis and characterization of cellulose acetate membranes fromoil palm empty fruit bunches (OPEFB) had been done. The purpose of this research is tofind out the characteristics of the cellulose acetate membrane from cellulose acetate ofOPEFB. The cellulose acetate membrane was prepared using the cellulose acetate (CA)and chloroform as solvent in the ratio 1:6, and the variations of polietilena glycol (PEG) asadditives were 10%, 20%, and 30% w/w. Membrane characterization was done inpermeability (flux), permselektivitas (rejection), and membrane morphology. The test wasperformed on water, T-70;; 1% w/v and T-500;; 1% w/v dextran solution. The resultsshowed that cellulose acetate membrane had the best characteristic in the addition ofPEG/S 10% w/w. The permeability was 55.54 L/m2hour in water, 18.48 L/m2hour fordextran T-70 and 5.14 L/m2hour for dextran T-500. The perm selectivity was 67.24% fordextran T-70 and 79.46% for dextran T-500. The SEM (Scanning Electron Microscope)analysis on membrane pore showed that the distribution of pore sizes is fine.Keywords : membrane, cellulose acetate, oil palm empty fruit bunches